Simulation and Implementation of RSCUAD Walking Robot Based on ROS and Gazebo Simulator - Andrean, Danu; Widodo, Nuryono Satya (Control Systems and Optimization Letters, 2023)
This research describes the virtual humanoid robot R-SCUAD using the Gazebo simulator. In its development, humanoid robots often perform movements that have a negative impact on the robot's hardware, therefore the development of a virtual robot model is a solution to overcome this problem. So that the robot can be simulated before running. Gazebo is a robot simulator that allows to accurately simulate, design and test robots in various environments. Gazebo itself is a simulation used by ROS (robotic operating system). The simulation is built by doing a 3D design process in solidwork software and exported to a URDF file that matches the format on the ROS. Tests carried out on robots are by comparing virtual robots with real robots. From the tests carried out on the robot, it was found that the virtual robot can walk according to the real robot, such as falling if the robot's condition is not balanced. The simulation robot also moves according to the real robot when the controls are carried out.